Hugo Puttaert : Think in colour - Puttaert, Hugo.; Cleeren, Steven; Poynor, Rick. (2014)
Ever since its foundation in 1990, design studio Visionandfactory has always played a prominent role in the Belgian & international graphic design scene. The studio's key figure is Hugo Puttaert, designer, professor, editor, publisher and one of the sector's movers and shakers. Instead of a complete overview, this book offers a selection, a kaleidoscopic view of Visionandfactory's multifaceted output. The selected work is contextualised with texts offering insight into the studio's history and work processes as well as into Hugo Puttaert's vision on design as a discipline and the social responsibility of the designer. With a split-fountain cover and hundreds of colour pages, this book provides a striking illustration of the credo that is so central to his vision, 'Think in Colour'.
boek
Keywords: Puttaert, Hugo